Revitalizing Faith-Based Philanthropy: Muhammadiyah’s Strategic ZISWAF Initiatives for Poverty Reduction and Human Capital Advancement - Muhammad Farhan; Achmad Soediro; Fardinant Adhitama; Eogenie Lakilaki (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines Muhammadiyah’s strategic governance of ZISWAF in South Sumatra, emphasizing its integration of Maqasid al-Shari’ah and the communal principle of Jama’ah. Using a qualitative approach with interviews and document analysis, the research highlights how Muhammadiyah shifted from informal charity practices to a professional, transparent, and decentralized model of Islamic philanthropy. The findings show that ZISWAF effectively supports education, healthcare, MSMEs, and asset-based empowerment, contributing to poverty alleviation and human capital development. The study offers a contextual model of Islamic social finance rooted in ethical governance and collective participation, with implications for faith-based institutions and policymakers. Future research should explore comparative cases and the role of digital technology in optimizing ZISWAF's impact.